EDUKASI DAN INOVASI PANGAN FUNGSIONAL DALAM MENGENDALIKAN STUNTING DI SEKOLAH-SEKOLAH KECAMATAN PINELENG KABUPATEN MINAHASA - Sudewi, Sri; Sutrisna, Agung; Nugraha, Mahendra Kusuma; Jayanto, Imam; Antasionasti, Irma (Jurnal Abdi Insani, 2024)
Stunting is a growth and development disorder in children caused by chronic malnutrition and recurrent infections characterized by substandard height. School children generally neglect breakfast because they are busy in the morning, easily bored with food consumed daily which is traditionally processed by boiling, stir-frying, frying, steaming. The majority of children and teachers in this school do not know clearly about stunting, its causes, impacts, and how to overcome it. This service aims to provide counseling on education about stunting and introduce local foods that can function as stunting prevention by making functional food innovations. The method was carried out by measuring the child's weight, height, and arm circumference as early indicators of stunting. Providing counseling to children and teachers about stunting, its causes, impacts, and how to overcome it and providing functional food innovation products processed from surrounding plants. The results of this service activity showed that the results of monitoring the measurement of weight, height, and arm circumference were 4 students whose body condition was below the ideal standard of children at MIN 1 Minahasa school. No body condition was found below normal standards at Ra Nurut Takwa Kindergarten school. Children's knowledge about stunting and the benefits of local plants in Sea Village that can be used as functional food has increased. Nutritious gifts containing high protein were also distributed to children in the form of milk, vitamin C, cheese, milk candy, jelly candy as a result of the Team's functional food product innovation whose material was sourced from comedy shows. This service can be concluded that education about stunting in children in schools has had a positive impact on improving health, increasing knowledge, monitoring potential and further prevention of stunting.